Development and Contemporary Understanding of Work-Based Learning - Morana Koludrović,; Rajić, Višnja (Revija za elementarno izobraževanje, 2024)
Serious criticism of didactic intellectualism in the past resulted in a range of pedagogical approaches to Work-based Learning as a response to this issue. A comparative overview of the development of work-based learning over time is presented in this article. Additionally, a temporal approach to work-based and workplace learning is explored. We see the change of WBL from being one part of individual pedagogical approaches to becoming part of policy recommendations. Finally, a discussion of the didactic features of contemporary Work-based Learning clearly positions it as a didactic model. The paper stresses the importance of WBL as a didactic model that is appropriate in all student-centred classrooms, regardless of the level of education.
Keywords: didactical model; work-based Learning; workplace learning; work-related learning, contemporary education.